2017
DOI: 10.1186/s12871-017-0305-7
|View full text |Cite
|
Sign up to set email alerts
|

Mild volume acute normovolemic hemodilution is associated with lower intraoperative transfusion and postoperative pulmonary infection in patients undergoing cardiac surgery -- a retrospective, propensity matching study

Abstract: BackgroundPerioperative allogenic transfusion is required in almost 50% of patients undergoing cardiac surgery and is associated with higher risk of mortality and morbidity (Xue et al., Lancet 387:1905, 2016; Ferraris et al., Ann Thorac Surg 91:944–82, 2011). Acute normovolemic hemodilution (ANH) is recommended as a potential strategy during cardiac surgery, but the blood conservation effect and the degree of ANH was still controversial. There is also an increasing concern about the improved outcomes associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 31 publications
0
26
1
2
Order By: Relevance
“…In a propensity score-matched retrospective analysis Zhou and colleagues reported that ANH was associated with decreased RBC transfusions and a decreased risk for postoperative pulmonary infections. 74 In a recently published meta-analysis that included 2,439 patients in 29 randomized controlled trials, ANH was associated with a reduced need for RBC transfusions and reduced postoperative bleeding. 75 It seems that in order to achieve maximal benefit of ANH, 800 mL or more of blood needs to be removed before surgery.…”
Section: Minimizing Hemodilutionmentioning
confidence: 99%
“…In a propensity score-matched retrospective analysis Zhou and colleagues reported that ANH was associated with decreased RBC transfusions and a decreased risk for postoperative pulmonary infections. 74 In a recently published meta-analysis that included 2,439 patients in 29 randomized controlled trials, ANH was associated with a reduced need for RBC transfusions and reduced postoperative bleeding. 75 It seems that in order to achieve maximal benefit of ANH, 800 mL or more of blood needs to be removed before surgery.…”
Section: Minimizing Hemodilutionmentioning
confidence: 99%
“…It appeared that the protective effect of ANH was related to the volume of blood removed, with patients in the 800 mL or greater group having fewer transfusions and better outcomes. A retrospective analysis conducted in cardiac surgical patients showed that although ANH decreased the intra‐operative RBC transfusion rate and the number of units transfused, no significant difference regarding post‐operative and total perioperative ABT was observed (Zhou et al, ). This lack of long‐term benefit could partly be explained by the small amount of blood removed in that study.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with TAAD undergoing surgical repair are at higher risk for postoperative infections. Because it usually mixed up a variety of risk factors which contribute to HAIs, such as cardiac surgeries (19), long duration of surgery time, mechanical ventilation. In this study, we firstly investigated the risk factors of HAIs for the patients with TAAD after surgical treatment.…”
Section: Discussionmentioning
confidence: 99%